Comparative Study of the Fast Track Method with the Crash Program Method in Accelerating Time and Costs (Universitas Iskandar Muda, 2024)
In many projects, delays are common, so it's important to make efforts to speed up the process and avoid them. This study investigates two methods of acceleration: the Fast Track method and the Crash Program method. The normal duration for this project is 180 days with a total cost of Rp. 14,666,588,288.29. The study uses MS Project to identify critical path activities that can be accelerated. The Fast Track method reduced the project time to 149 days at a cost of Rp. 14,287,701,424.18, while the Crash Program method reduced it to 144 days at a cost of Rp. 14,318,586,553.16. The study compares the time and cost outcomes of the two methods. The difference is due to the Fast Track method not incurring an increase in direct costs, only reducing indirect costs by changing predecessors. On the other hand, the Crash Program method resulted in additional direct costs but reduced indirect costs by adding 2 hours of overtime work.